Synthesis, characterization and 2,5-pyridinedicarboxylic acid interaction of Zinc(II) complexes with N-(4-X-phenyl)pyridine-2-yl-methanimine ligands (X= -Cl and -N(CH3)2) (Communications in Inorganic Synthesis, 2017)
Abstract: Two new Zn(II) N-(4-X-phenyl)pyridine-2-yl-methanimine complexes, [Zn(NN´-Cl)Cl2](1) and [Zn(NN´-N(CH3)2)Cl2](2), have been synthesized and characterized byÂ elemental analysis, FT-IR and NMR-1H spectra. The crystal structure of complex 1 was determined by X-ray single crystal diffraction. Experiments performed by Benesi-Hilderbrand method indicate that zinc complexes interact with 2,5-pyridinedicarboxyc acid.